Thunderstorm dynamics in a scale interaction - Dias, Maria Assunção F. Silva (Ciência e Natura, 2000)
This paper presents a review of thunderstorm dynamics through the use of the vorticity equation with a focus on the development of rotation, an indicator of storm severity. The processes involved in the scale interaction are basically the tilting of vortex tubes while the divergence (or ballerina) term, being highly non-linear, provides intensification of incipient vorticity. A brief account of numerically simulated storms in Brazil with well defined wind shear in the storm environment is presented.